Book Notes - Overland, Orm (American Studies in Scandinavia, 1975)
- Anna Katona’s ’Hungarian Studies in English - Kate Chopin’s ’The Storm and other Stories; with the Awakening’. Edited with an introduction by Per Seyersted - Marcus Raskin’s ’Notes on the Old System: To Transform American Politics’ - ’Letters from the Promis Land: Swedes in America 1840-1914’ edited by H. Arnold Barton - Arnfinn Bruflot’s ’Dei kom til Amerika’ ("They came to America")